Do the ESC guidelines improve the treatment of acute myocardial infarction due to acute circumflex artery occlusion?. (25th November 2020) - Simek, S; Kral, A; Kovarnik, T; Zemanek, D; Anger, Z; Lubanda, J.-C; Linhart, A
Abstract: Background: The left circumflex artery (LCX) and its branches are less often recognized as infarct related artery (IRA) in STEMI compared to NSTEMI patients because of lower ability to detect posterior AMI on 12leads ECG. Significant proportion of patients with acute LCX occlusion therefore did not receive immediate reperfusion therapy. The recent ESC guidelines recommendation of immediate coronary angiography for NSTEMI with ongoing ischemia should change the situation. Objectives: To estimate the change in proportion of patients receiving immediate reperfusion therapy for acute LCX occlusion within last 20 years. Methods: Prospective registry of patients with acute coronary syndromes treated in the cardiac centre. The group of patients treated with direct PCI as STEMI and the group of patients treated as NSTE ACS were compared. Results: Of 369 STEMI patients treated with primary PCI in 1995–2000, the LCX was recognized as IRA in only 29 (8%) patients. In the group of 809 STEMI patients treated in period 2008–2011, the LCX was detected as IRA in 133 (16%). In he recent group of 1006 patients treated as STEMI in period 2016–2019 the LCX was IRA in 166 (16.5%) patients. LAD, LM and RCA were detected as IRA in 407 (40.5%), 17 (1.7%) and 415 (41%) patients respectively. In the parallel group of 1087 NSTE-ACS patients the proportion of LCX, LAD, LM and RCA as culprit artery was 271 (25%), 438 (40%), 52 (5%) and 326 (30%) respectively. The difference of LCX involvement in STEMI (16%) compared to NSTE-ACS patients (25%) was highly significant (p<0, 001). Conclusion: The disproportion of LCX involvement among the patients with STEMI and NSTE-ACS is not decreasing in the course of last 10 years. Our data show that still significant part of patients with acute LCX occlusion are diagnosed as having NSTE-ACS and are not treated with adequate immediate reperfusion. So even in recent era of modern reperfusion therapy these patients which mostly suffer posterior AMIs have a lower chance to receive the proper treatment in our region. The new ESC guidelines did not change this fading yet. Better diagnostics of AMI due to the acute LCX occlusion (including 15 leads ECG) is routinely needed or every suspected NSTEMI patient should undergo the acute coronary angiogram as he would be a STEMI patient. Funding Acknowledgement: Type of funding source: None